Innovative geometric design improves the resistance of simple metal / metal lap joint - Mehadjia Bezzerrouki; Kouider Madani; Abderrahmane Sahli; Sbastien Touzain; Stphanie Mallarino (Fracture and Structural Integrity)
Bonded assemblies are widely used in many industrial sectors mainly in the aerospace field. Many researches in these domains are focused on evaluating the stresses in the adhesive layer in order to achieve maximum strength and long service life. Factors that affect joint design are the mechanical and physical properties of the adhesive and the substrate. The reduction of stress concentration at the edges of the adhesive provides the strength of the adhesive layer. Our work fits in this context, based on the ASTM D1002 standard. The innovative idea of this paper is to bring geometric improvements to an assembly system type Aluminum/Aluminum 2024-T3 bonded with an adhesive ADEKIT A-140. The analysis of the stress distribution is performed by the three-dimensional finite element method using the ABAQUS calculation code. The geometric improvements presented in this work are beneficial and the results show a good reduction of the stress concentration along overlap length.